2016
DOI: 10.1212/wnl.0000000000003221
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study in multiple system atrophy

Abstract: Objective:To identify genetic variants that play a role in the pathogenesis of multiple system atrophy (MSA), we undertook a genome-wide association study (GWAS).Methods:We performed a GWAS with >5 million genotyped and imputed single nucleotide polymorphisms (SNPs) in 918 patients with MSA of European ancestry and 3,864 controls. MSA cases were collected from North American and European centers, one third of which were neuropathologically confirmed.Results:We found no significant loci after stringent multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
138
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 39 publications
4
138
1
1
Order By: Relevance
“…These findings are in line with the results of previous small studies (n= 22; 59; 47; 40 and 12) 1014 and no signal at the APOE locus in the recent genome-wide association study of 331 pathologically-confirmed MSA patients. 15 It also is worth noting that in agreement with these findings, a recent study reported no association between rapid eye movement sleep behavior disorder (which could be a clinical prodromal feature preceding the development of MSA) and risk of MSA. 16 …”
Section: Discussionsupporting
confidence: 67%
“…These findings are in line with the results of previous small studies (n= 22; 59; 47; 40 and 12) 1014 and no signal at the APOE locus in the recent genome-wide association study of 331 pathologically-confirmed MSA patients. 15 It also is worth noting that in agreement with these findings, a recent study reported no association between rapid eye movement sleep behavior disorder (which could be a clinical prodromal feature preceding the development of MSA) and risk of MSA. 16 …”
Section: Discussionsupporting
confidence: 67%
“…25 In MSA, contradicting results have been reported regarding the SNCA locus, and the largest analysis thus far refuted the previously reported association. 26 In the current study, we aimed to thoroughly analyze the SNCA locus in RBD. We used a combination of full SNCA sequencing and comprehensive SNP genotyping in the largest genetic study of iRBD to date, as well as in PD and DLB patients with and without pRBD, to examine SNCA association with RBD risk and phenoconversion from RBD to defined neurodegenerative disease.…”
mentioning
confidence: 99%
“…In light of these observations, it could also be concluded that there may exist a genetic predisposition for oligodendrocytes to develop abnormal α-syn accumulation (Sturm et al, 2016). The genetic risk factors with the most evidence in MSA are variants in the SNCA and COQ2 genes (Collaboration, 2013; Scholz et al, 2009), however genome-wide association studies have failed to find association between common genetic variations in those genes and MSA (Sailer et al, 2016). …”
Section: The Neuropathology Of Msamentioning
confidence: 99%